Influence of Prey Species on Feeding Preference, PostEmbryonic Development and Life Span of Cheilomenes Sexmaculata (Fabricius) - Kumar, Md. Sanjeev; Ahmad, Equbal; Rakhshan, Rakhshan (European Scientific Journal, ESJ, 2016)
Coccinellid beetles due to high foraging performance, immense predatory potential and high reproductive efficacy possess the potential to be effectively employed in biological control programme for several destructive insects such as aphids, coccids, scale insect etc. Cheilomenes sexmaculata is very common in the target area and found abundantly predating on several aphids. Hence, the feeding performance and post embryonic development of C. sexmaculata feeding on three economically important aphids, Aphis craccivora, Aphis gossypii and Lipaphis erysimi have been studied. The grubs of the predator, C. sexmaculata showed greater preference for A. craccivora (141.4± 6.67 aphids) followed by A. gossypii (122.25 ± 7.44 aphids) and L. erysimi (106.95 ± 7.73 aphids). The higher development period was observed on L. erysimi (17.50 ± 0.72 days) than A. gossypii (16.0 ± 0.5 days) and A. craccivora (15.6± 0.24 days). Similarly C. sexmaculata had higher pre-pupal and pupal period when fed on L. erysimi than A. gossypii and A. craccivora. The higher longevity of the C. sexmaculata was observed on A. craccivora (39.6 ± 1.21 days) than A. gossypii (35.25 ± 0.47 days) and L. erysimi (33.25 ± 0.47 days). It is probably due to more preference of A. craccivora than A. gossypii and L. erysimi. Hence, this predator consumed more A. craccivora than A. gossypii and L. erysimi during its life span and also during larval development period.